The physiology of singing and implications for ‘Singing for Lung Health’ as a therapy for individuals with chronic obstructive pulmonary disease - Adam Lewis; Nicholas S Hopkinson; Keir Elmslie James Philip; Phoene Cave; Adam Lound; Juliet Russell (BMJ Open Respiratory Research)
Singing is an increasingly popular activity for people with chronic obstructive pulmonary disease (COPD). Research to date suggests that ‘Singing for Lung Health’ may improve various health measures, including health-related quality-of-life. Singing and breathing are closely linked processes affecting one another. In this narrative review, we explore the physiological rationale for ‘Singing for Lung Health’ as an intervention, focusing on the abnormalities of pulmonary mechanics seen in COPD and how these might be impacted by singing. The potential beneficial physiological mechanisms outlined here require further in-depth evaluation.